Controlling ammonia volatilization by mixing urea with humic acid, fulvic acid, triple superphosphate and muriate of potash - Shamsuddin, Rosliza; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: Inefficient use of inorganic fertilizer such as urea is caused by substantial losses of ammonia when urea is surface-applied. Ammonia losses can be controlled by adding acidic material such as TSP, HA or FA. In order to reduce ammonia loss and retain soil exchangeable ammonium and available nitrate as well as producing complete organic based fertilizer, this study was conducted to compare the effects of urea-TSP-MOP, urea-TSP-MOP-HA, urea-TSP-MOP-FA, urea-TSP-MOP-acidified (HA + FA) mixtures on ammonia loss, soil pH, soil exchangeable ammonium and available nitrate accumulation compared to urea alone. Approach: The effects of urea amended with or without TSP, MOP, HA and FA were evaluated in a laboratory condition using a closed-dynamic air flow system. Ammonia loss, soil pH, soil exchangeable ammonium and available nitrate were determined using standard procedures. Results: Urea-TSP-MOP-HA, Urea-TSP-MOP, Urea-TSP-MOP-FA and Urea-TSP-MOP-Acidified (HA + FA) mixtures significantly reduces ammonia loss by 12.92, 20.12, 29.54 up to 100 % compared to urea alone. The same observation was made for soil exchangeable ammonium. From all the treatments, only Urea-TSP-MOP-FA and Urea-TSP-MOP-Acidified (HA + FA) significantly retained soil available nitrate accumulation and the findings were consistent with pH found in the study. It must be stressed that results obtained in the incubation experiment using an acidic (pHwater 6.32) soil of Typic Paleudults (Bekenu series) might only be applicable to similar acid soils. Conclusion: Urea, TSP and MOP amended with HA or HA and FA significantly reduced ammonia loss. The outcome of this study may contribute to the improvement of urea N, P and K use efficiency as well as reducing environmental pollution.